Pemanfaatan Media Sosial WhatsApp sebagai Strategi Personal Selling Digital UMKM Kecamatan Tandes - Mochamad Rizki Rahman; Nurkholish Majid (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
In the digital era, Micro, Small, and Medium Enterprises (UMKM) are constantly required to adapt to technological developments, and the ability to build direct communication with customers has become an important aspect in increasing business competitiveness. However, several UMKM in Tandes Subdistrict have not yet optimally utilized social media as a means of digital personal selling. This condition has resulted in ineffective marketing processes and interactions with customers. This mentoring activity aims to improve the knowledge and skills of UMKM players in implementing digital personal selling strategies through WhatsApp and promotion by creating attractive content designs. The implementation method includes education related to the concept of digital personal selling and assistance in creating promotional designs for WhatsApp statuses. The results of the activity show an increase in the ability of UMKM players to communicate with potential customers in a more professional manner and to produce more attractive promotional content designs through WhatsApp statuses.